UTANG UNTUK RAKYAT - hudiyanto hudiyanto (Universitas Muhammadiyah Yogyakarta, 2010)
Indonesia is the famous country that has a large amount of foreign debt. Until year 2000, Indonesia has the foreign debt about US$120 milliard, and it is more than psychological threshold (US$ 100 milliard). Some economist said that when the country has foreign debt more US$ 100 milliard, so the country is in the “debt trap” condition. Fisher also said if the country has the new foreign debt per year less than debt repayment per year, so the country is in “debt crisis” condition. This article will discuss about how Indonesia can exit from the debt crisis or debt? Did the foreign debt use for Indonesian people?